Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

When deriving the equation for the impulse-momentum theorem, the following occurs:

$$\cdots=\int\limits_{t_1}^{t_2}\frac{d\vec p}{dt}dt = \int\limits_{\vec p_1}^{\vec p_2}d\vec p=\cdots$$

I know the $dt$s aren't simply canceling each other out, so why can we get rid of them and then why do the limits of integration change? Is it because once the $dt$s are gone the limits just change automatically since we're only left with $d\vec p$ or is there something that needs to be done and it just happens that the limits change because of it?

Thank you for your time.

share|cite|improve this question
Compare with $\int_a^b f'(x)\, \mathrm dx=f(b)-f(a)=\int_{f(a)}^{f(b)}\mathrm dx$. – Hagen von Eitzen Jul 29 '14 at 21:32
It's just the substitution rule, really. You might also compare it notationally with a typical statement of the chain rule: $\dfrac{dp}{du}=\dfrac{dp}{dt}\dfrac{dt}{du}$. ('Toss out' the $du$ in there, and you've got your statement.) Note though that this is just shorthand for the math. – Semiclassical Jul 29 '14 at 21:36
@HagenvonEitzen and Semiclassical Thank you for your comments, I think that makes sense. – John Jul 29 '14 at 21:49
It might be pedagogically useful to use the term "differentiation by substitution" instead of "chain rule". – Michael Hardy Jul 29 '14 at 22:09
up vote 1 down vote accepted

This is the chain rule. Sometimes the chain rule is stated as $\dfrac{dy}{dx}=\dfrac{dy}{du}\cdot\dfrac{du}{dx}$, just as if $du$ literally refers to a number and cancels.

$$ \int_a^b \frac{dp}{dt}\,dt = \int_{t=a}^{t=b} f'(p(t))p'(t)\,dt \tag 1 $$ where $f'$ is a constant function equal to $1$. So $f(p)=p+\text{constant}$. So by the chain rule $(1)$ is $$ \int_{t=a}^{t=b} (f\circ p)'(t)\,dt = f(p(b))-f(p(a)) = \int_{p=p(a)}^{p=p(b)} f'(p)\,dp = \int_{p=p(a)}^{p=p(b)} 1\,dp. $$

share|cite|improve this answer
Thank you very much. – John Jul 29 '14 at 22:24

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.